2009
DOI: 10.1002/jmv.21426
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to symptomatic norovirus infection in Nicaragua

Abstract: Host genetic resistance to Norovirus (NoV) has been observed in challenge and outbreak studies in populations from Europe, Asia, and USA. In this study, we have investigated if histo-blood group antigens can predict susceptibility to diarrhea caused by NoV in Nicaragua, Central America, and if this can be reflected in antibody-prevalence and titer to NoV among individuals with different histo-blood group antigen phenotypes. Investigation of 28 individuals infected with NoV and 131 population controls revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 39 publications
7
67
2
2
Order By: Relevance
“…The prevalence of the Le aϩ phenotype in Vietnamese children is similar to that reported for other countries from this region (48,49). The partial secretor (Le aϩbϩ ) phenotype observed in Asian populations is quite unique and might be associated with high levels of susceptibility to NoV. A study in Nicaragua showed an absence of this phenotype in both NoV-infected and control groups (50). In addition, that study found that greater proportions of secretors than nonsecretors developed antibodies to NoV and higher antibody titers were induced in secretors than in nonsecretors, indicating that nonsecretors may develop less-robust immune responses following vaccination for the virus (50).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The prevalence of the Le aϩ phenotype in Vietnamese children is similar to that reported for other countries from this region (48,49). The partial secretor (Le aϩbϩ ) phenotype observed in Asian populations is quite unique and might be associated with high levels of susceptibility to NoV. A study in Nicaragua showed an absence of this phenotype in both NoV-infected and control groups (50). In addition, that study found that greater proportions of secretors than nonsecretors developed antibodies to NoV and higher antibody titers were induced in secretors than in nonsecretors, indicating that nonsecretors may develop less-robust immune responses following vaccination for the virus (50).…”
Section: Discussionsupporting
confidence: 81%
“…The partial secretor (Le aϩbϩ ) phenotype observed in Asian populations is quite unique and might be associated with high levels of susceptibility to NoV. A study in Nicaragua showed an absence of this phenotype in both NoV-infected and control groups (50). In addition, that study found that greater proportions of secretors than nonsecretors developed antibodies to NoV and higher antibody titers were induced in secretors than in nonsecretors, indicating that nonsecretors may develop less-robust immune responses following vaccination for the virus (50). In a study in Burkina Faso, which demonstrated an absence of Le aϩbϩ antigens and a high prevalence (32%) of Le aϪbϪ antigens, a strong association between NoV infection and secretor status was identified, with the exception of two cases of GII.4 and GII.7 infections in nonsecretors (35).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the homotypic distribution of HBGAs in the subset of 500 macaques tested, recovirus infection could not be linked to a particular HBGA type, although both type B and type O macaques were infected with recoviruses. Future studies of macaques possessing more-heterogeneous HBGA distribution are needed to determine a potential association between HBGA phenotypes and susceptibility to recovirus infection in a population-based study as described for NoVs (3,23,35).…”
Section: Resultsmentioning
confidence: 99%
“…Norovirus GII.17 is of clinical relevance as it has been implicated in nosocomial NoV infection (Sukhrie et al 2011) and chronic NoV infection in a kidney transplant patient (Schorn et al 2010). The genotype has also been widely reported in children with gastroenteritis in Central and South America (Bucardo et al 2009;Ferreira et al 2012;Gomes et al 2008), Korea (Park et al 2011) and Thailand (Kittigul et al 2010). …”
Section: Discussionmentioning
confidence: 99%